Semaphorin 7A promotes endothelial permeability and inflammation via plexin C1 and integrin β1 in Kawasaki disease - Junhua Huang; Chuanmei Zhao; Shuwan Zhang (BMC, 2024)
Abstract Background Kawasaki disease (KD) is a pediatric systemic vasculitis characterized by endothelial cell dysfunction. Semaphorin 7A (Sema7A) has been reported to regulate endothelial phenotypes associated with cardiovascular diseases, while its role in KD remains unknown. This study aims to investigate the effect of Sema7A on endothelial permeability and inflammatory response in KD conditions. Methods Blood samples were collected from 68 KD patients and 25 healthy children (HC). The levels of Sema7A and A Disintegrin and Metalloprotease 17 (ADAM17) in serum were measured by enzyme-linked immunosorbent assay (ELISA), and Sema7A expression in blood cells was analyzed by flow cytometry. Ex vivo monocytes were used for Sema7A shedding assays. In vitro human coronary artery endothelial cells (HCAECs) were cultured in KD sera and stimulated with Sema7A, and TNF-α, IL-1β, IL-6, and IL-18 of HCAECs were measured by ELISA and qRT-PCR. HCAECs monolayer permeability was measured by FITC-dextran. Results The serum level of Sema7A was significantly higher in KD patients than in HC and correlated with disease severity. Monocytes were identified as one of the source of elevated serum Sema7A, which implicates a process of ADAM17-dependent shedding. Sera from KD patients induced upregulation of plexin C1 and integrin β1 in HCAECs compared to sera from HC. Sema7A mediated the proinflammatory cytokine production of HCAECs in an integrin β1-dependent manner, while both plexin C1 and integrin β1 contributed to Sema7A-induced HCAEC hyperpermeability. Conclusions Sema7A is involved in the progression of KD vasculitis by promoting endothelial permeability and inflammation through a plexin C1 and integrin β1-dependent pathway. Sema7A may serve as a potential biomarker and therapeutic target in the prognosis and treatment of KD.